Development Status of IRWs Steering and Application Trend of PMSM in LRVs - Cheng ZHOU; Kunlai LEI; Daitao SUN; Maoru CHI (机车电传动)
In order to promote the development of the low-floor light rail vehicles (LRVs) and expand the scope of the independently rotating wheelsets (IRW), development status of IRWs steering and application trend of permanent magnet synchronous direct-driven motor (PMSM) in LRVs were reviewed. Steering is the main problem that limits the application of IRW, and the main steering strategies include rotating coupling method and active control method through the analysis of the steering principle. At present, the wheel rotational speed coupling method is widely used, such as Alstom’s lateral coupling and Siemens’ longitudinal coupling. The active control steering is the development trend of independent wheelset steering, which can obtain better steering ability. At present, there are speed control methods that are used in Adtranz vehicle. In the active control steering, the speed control does not need additional actuator, which is easier to realize, but at the same time, the layout and selection of the motor should be considered comprehensively. Because of the lack of deceleration link, it is easy to realize low-speed and high torque operation. The speed control is realized by PMSM, which has become one of the future development directions of LRV.